Communication and society:senior virtual university's contribution to sustainability during the pandemic perio - Galinha, Sónia (2022)
Lifelong Learning (LLL) and Sustainable Human Development (HDI) are defended by ONU focused on their educational goals and quality of life. Objective: In the pandemic period an attempt was made to evaluate the contributions of the new experience of the Senior Virtual University (SVU): the perceptions and participation in training activities and the correlation between variables. Method: This is a quantitative, cross-sectional, and correlational study involving 86 senior virtual university students, using beyond a demographic questionnaire the USVSOQ scale. Results:The USVSOQ scale has a good internal consistency (Cronbach's Alpha coefficient=0.82). There is a positive correlation (rho=0.6) and statistically significant (p<0.001) between satisfaction with the SVU and the continuity of participation of its students for the next academic year. The SUV offer is inclusive, transversal and covers the whole country. The association between suggestions for SVU improvement to be implemented in the next school year and gender is highlighted (p-value = 0.04). Conclusion: SVU prove to be a contribution to sustainability in education in periods of confinement and emergency, upskilling.